Perkembangan Kriminalitas Lokal Borneo Awal Tahun 1982 - Fitriyani, Ema; Michael Silvester Mitchel Vinco; Jamil, Jamil (History Education Department, Universitas Mulawarman, 2023)
This research aims to examine the development of crime in Borneo in early 1982 based on archival data from the 1982 Borneo Newspaper. This research uses a historical approach by analyzing archival documents related to criminal incidents in Borneo during that period. The aim of this research is to examine the differences in crime levels that occurred in Borneo in early 1982, the factors that influenced them, and their impact on society and security in the region. The research results show that in early 1982, Borneo experienced a significant increase in crime cases. Crime cases such as theft, robbery and violence have increased drastically. Factors that influenced the development of crime in Borneo during this period included political instability, economic inequality and social changes that occurred in the region. The impact of this development in crime is being felt by the people of Borneo. This research contributes to understanding the history of the development of crime in Borneo in early 1982. The results of this research can be a reference for further research regarding crime in the region. In addition, this research also provides a better understanding of the factors that influence the development of crime and its impact on society and security in Borneo.